THE IMPORTANCE OF MODERN TECHNOLOGIES, INNOVATIVE PROGRAMS AND SYSTEMS IN EDUCATION - Begimkulova Dilobar; Rustamova Mohinur Xurshid qizi (Journals Park Publishing, 2024)
This article discusses various programs used in teaching schoolers and students , their role in the organization of lessons, and new digital systems In education.
Keywords: Technology, smart , e-learning, electronic class, individual education, distance education, MOODLE, Hemis, Duolingo, Hot Potato.